Bone density in children: what are we measuring?. Issue 11 (25th April 2019) - Shaw, Nick; Crabtree, Nicola
Abstract : The measurement of bone density is a frequent request in the assessment of children with concerns about bone health due to chronic disease or recurrent fractures. Dual energy X-ray absorptiometry (DXA) remains the recommended modality and is widely available. However, the interpretation and reporting of results in growing individuals needs to be undertaken by individuals who are familiar with scanning children and the potential pitfalls.